Adaptation to flooding in low‐income urban settlements in the least developed countries: A systems approach. Issue 3 (10th June 2020) - Haque, Anika Nasra; Bithell, Mike; Richards, Keith S.
Abstract : This study aims to use a whole systems approach (1) to understand the processes of adaptation to flooding of the urban poor; (2) to identify new knowledge of how low‐income settlements might better adapt to climatic risks; and (3) to begin to develop appropriate guidance on this. Low‐income urban settlements in the least developed countries (LDCs) present an extreme case where catastrophic natural hazards and chronic social hazards overlap. These low‐income urban populations face the greatest adaptation challenges as they often occupy informal settlements that are particularly exposed to hazards, and have multiple vulnerabilities arising from their lack of basic services. There is a dynamic complexity of issues arising from the many levels of actor involved and multiple social and physical factors. Analysing such a complex phenomenon calls for a specific conceptual framing, and a systems theory approach is suggested to provide a holistic perspective. The case study for this research is located in Dhaka East, where there is both high vulnerability to flooding, and a significant low‐income population. The research has adopted a mixed methods approach involving different data collection methods governed by the different scales and actors being investigated. The research develops new systems understandings of perceptions and experiences of the local population about adaptation processes in low‐income urban settlements, and how these processes may be positively influenced by integrating bottom‐up and top‐down approaches. Abstract : The processes of adaptation to flooding of the urban poor are complex phenomenon: there is a dynamic complexity of issues arising from the many levels of actor involved and multiple social and physical factors. Analysing such a complex phenomenon calls for a specific conceptual framing, and a systems theory approach is suggested to provide a holistic perspective. The research develops new systems understandings of perceptions and experiences of the local population about adaptation processes in low‐income urban settlements, and how these processes may be positively influenced by integrating bottom‐up and top‐down approaches.